Ser un papá comprometido: ¿Qué significa esto? - Kate Fogarty; Garret D. Evans (EDIS)
What exactly does it mean to be an involved father, and how does one go about having a healthy and involved relationship with one’s child? Find out in this 5-page Spanish-language fact sheet written by Kate Fogarty and Garret D. Evans and published by the UF Department of Family Youth and Community Sciences, May 2011.